Tricuspid atresia and pulmonary atresia in a child with Rubinstein-Taybi syndrome - Rohit S Loomba; Gabrielle Geddes (Wolters Kluwer Medknow Publications, 2015)
Rubinstein-Taybi syndrome is a well-characterized condition causing distinctive physical characteristics, intellectual disability, and multiple congenital malformations. Cardiac abnormalities are found in a third of individuals with this condition and usually consist of isolated septal defects or patent ductus arteriosus, although more complex congenital lesions have been described. We present the first reported case of tricuspid atresia and pulmonary atresia with hypoplasia of the right ventricle in the setting of Rubenstein-Taybi syndrome.